2018
DOI: 10.1515/psicl-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal approach to the analysis of gender stereotypes in contemporary British TV commercials: “women and men at work”

Abstract: Abstract The aim of this article is to examine the meaning potential of images in the enactment or creation of gender stereotypes in a corpus of contemporary British TV commercials. The dimensions outlined in Goffman (1979) and some aspects of Kress and van Leeuwen’s (1996, 2006) metafunctions are taken as a starting point to quantitatively and qualitatively analyse a sample of 155 ads which depict women and men in working settings. Findings indicate that women are mainly portr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…In a virtual world, Norwak and Rauh (2005) found that female avatars are considered friendly, caring, helpful and emphatic and thus, people prefer to interact with female avatars than males. However, a high social position is related more closely to the perceived expertise of a male agent than a female agent (Rubio, 2018). That is, being a male strengthens the effect of social position on perceived expertise.…”
Section: Role Of Virtual Avatarsmentioning
confidence: 89%
See 1 more Smart Citation
“…In a virtual world, Norwak and Rauh (2005) found that female avatars are considered friendly, caring, helpful and emphatic and thus, people prefer to interact with female avatars than males. However, a high social position is related more closely to the perceived expertise of a male agent than a female agent (Rubio, 2018). That is, being a male strengthens the effect of social position on perceived expertise.…”
Section: Role Of Virtual Avatarsmentioning
confidence: 89%
“…3.1.3 Interaction between social position and gender. Many researchers have pointed out that some stereotypical social roles are historically assigned to different genders (Hetsroni and Lowenstein, 2014;Marlow and Patton, 2005;Rubio, 2018). As Marlow and Patton (2005, p.…”
Section: Role Of Virtual Avatarsmentioning
confidence: 99%
“…Many scholars started analyzing print ads, posters, political speeches, political cartoons, movies, etc. from a multi-modal perspective (e.g., Helland, 2018;Lirola, 2016;Michelson & Álvarez Valencia, 2016;Oyebode & Unuabonah, 2013;Rubio, 2018)…”
Section: Context Of the Studymentioning
confidence: 99%
“…Gender issues have long been the focus of attention and sparked a lot of research in social and linguistic studies. Several studies have tackled gender representation from a multimodal perspective in different genres, including English language textbooks (Ahmad & Shah, 2019;Marefata & Marzban, 2014), TV commercials (Rubio, 2018), cinematic content (Guha et al, 2015) and young children's popular culture (Lindstrand et al, 2016). In these studies, the issue of how image representation and the combination of different participants contribute to constructing gender roles for men and women was examined.…”
Section: Gender Representation and Multimodal Discoursementioning
confidence: 99%